Rhetorical annotations about ineffective succession in Cicero’s De inventione and the Rhetorica ad Herennium - Cassarino, Alessandro (Ciceroniana On Line, 2023)
This contribution deals with the interplay between rhetoric and law, and how the former was the originator of the procedural institution of the querela inofficiosi testamenti. In particular, we focus on the well-known case of the matricide Malleolus, sentenced to capital punishment, in order to understand or not the validity of his will through the use of analogical legal argumentation (ratiocinatio).